2022
DOI: 10.1177/10556656221132031
|View full text |Cite
|
Sign up to set email alerts
|

Thai CLEFT-Q: Phase 1—A Pilot Study of Translation and Cultural Adaptation in Thailand

Abstract: To translate and culturally adapt the original English version of the CLEFT-Q into Thai (Thai CLEFT-Q). A pilot study. A single tertiary referral hospital in Thailand. Patients with cleft lip or palate (CL/P) aged between 8 and 29 years. The CLEFT-Q was translated and culturally adapted from English into Thai using the good practice guidelines developed by the International Society for Pharmacoeconomics and Outcomes Research (ISPOR). Two forward translations and reconciliation, 1 back translation, and 2 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…In our case, we used a text-based table with a common set of normative values to visualize results regardless of cleft type, despite prior development of more refined methods for their display. 20 Finally, this study was implemented at an urban, tertiary care center with a large multidisciplinary cleft and craniofacial team, relying on collaborators from our clinical informatics team to guide and support PRO implementation. Assistance from an EHR analyst with the necessary training and permissions to configure EHR software was essential.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we used a text-based table with a common set of normative values to visualize results regardless of cleft type, despite prior development of more refined methods for their display. 20 Finally, this study was implemented at an urban, tertiary care center with a large multidisciplinary cleft and craniofacial team, relying on collaborators from our clinical informatics team to guide and support PRO implementation. Assistance from an EHR analyst with the necessary training and permissions to configure EHR software was essential.…”
Section: Discussionmentioning
confidence: 99%
“…CLEFT-Q continues to undergo translation and validation to other languages worldwide [63][64][65][66]. Multiple studies have demonstrated the validity and utility of CLEFT-Q [67] and the ICHOM standard set to the extent that, at this point, research is moving beyond content validity and focusing on the feasibility of implementation and verifying scales for their utility in clinically significant decision making.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…Institutional support and financial resources are vital to effective adoption and implementation, which can be a Outcomes Measurement (ICHOM) has also produced a standard set of standardized outcome measures [62] that is also commonly used by cleft teams for the comprehensive appraisal of cleft care (see Figure 2). CLEFT-Q continues to undergo translation and validation to other languages worldwide [63][64][65][66]. Multiple studies have demonstrated the validity and utility of CLEFT-Q [67] and the ICHOM standard set to the extent that, at this point, research is moving beyond content validity and focusing on the feasibility of implementation and verifying scales for their utility in clinically significant decision making.…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…This instrument represents a significant advancement in the field of cleft care, providing a comprehensive and validated tool to assess a wide range of outcomes relevant to patients with CLP. Its development involved a significant international effort, encompassing psychometric analyses and the establishment of normative values based on a large sample of children and young adults from various countries [7,9]. This global perspective ensures the applicability of the CLEFT-Q in different cultural and healthcare contexts, making it an invaluable instrument for clinicians and researchers.…”
Section: Introductionmentioning
confidence: 99%